2017
DOI: 10.1186/s13048-017-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-205 promotes cell invasion by repressing TCF21 in human ovarian cancer

Abstract: BackgroundOvarian cancer is the leading lethal, gynecological malignancy in the United States. No doubt, the continued morbidity and mortality of ovarian cancer reflects a poor understanding of invasive mechanisms. Recent studies reveal that ovarian cancers express aberrant microRNAs (miRNAs or miRs), some of which have oncogenic or tumor suppressor properties. Several studies suggested that miR-205 is involved in tumorigenesis. Presently, we investigate the molecular mechanisms and target of miR-205 in ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 44 publications
5
42
1
Order By: Relevance
“…And miR-1 inhibited cell migration and proliferation in OC through c-Met pathway [10]. But miR-205 accelerated cell invasion by repressing TCF21 in human OC [11]. And miR-216a facilitated the metastasis and EMT of OC by suppressing the PTEN/AKT pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…And miR-1 inhibited cell migration and proliferation in OC through c-Met pathway [10]. But miR-205 accelerated cell invasion by repressing TCF21 in human OC [11]. And miR-216a facilitated the metastasis and EMT of OC by suppressing the PTEN/AKT pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al and others (34) found that TCF21 can target PI3K/Akt and ERK signal pathways, thus inhibiting tumor-associated angiogenesis and cholangiocarcinoma growth. Many evidences show that TCF21 is regulated by miRNAs, such as miR526b (35), miR-205 (36), which can inhibit tumor development. Zhou et al (37) found that microRNA-30-3p targeting TCF21 inhibited endothelial cell injury induced by in ammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al and others (34) found that TCF21 can target PI3K/Akt and ERK signal pathways, thus inhibiting tumor-associated angiogenesis and cholangiocarcinoma growth. Many evidences show that TCF21 is regulated by miRNAs, such as miR526b (35), miR-205 (36), which can inhibit tumor development. Zhou et al (37) found that microRNA-30-3p targeting TCF21 inhibited endothelial cell injury induced by inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%